Examining the underlying exposures of hit-and-run and non-hit-and-run crashes. (March 2021) - Jiang, Xinguo; Han, Mingqiang; Guo, Runhua; Zhang, Guopeng; Fan, Yingfei; Li, Xiang; Bai, Wei; Wei, Mengmeng; Liang, Qi
Abstract: Introduction: Hit-and-run crashes occur when the driver at fault leaves the scene without reporting, which could delay emergency response for the victims who are left. For this reason, it is assumed that hit-and-run crashes lead to more serious injuries; however, the research in this area is limited. The objectives of the study are to examine the differences in hit-and-run and non-hit-and-run victim injury severities and to identify the factors that may influence any differences. Methods: Quasi-induced exposure technique, an indirect method, is employed to measure the relative crash exposures between hit-and-run and non-hit-and-run crashes using Michigan two-vehicle injury crashes 2012–2014. Random parameter ordered logit model is used to reveal the discrepancy of the factors contributing to victim injury severity. Results: We found that the injuries sustained by the drivers left at the scene (victims) of hit-and-run crashes were generally less severe compared to non-hit-and-run driver victims, which may be attributed to the differential crash factors in terms of driver age and vehicle type. The injury-severity contributing factors of hit-and-run crashes differed considerably from the non-hit-and-run crashes. Characteristics such as occurring in rural areas, at nighttime, at intersections, crash type, and alcohol involvement significantly increased the injury severities of the driver victims. Conclusion: We inform the hit-and-run literature to suggest a contradiction to the assumption that leaving the crash scene may lead to more serious injuries. This example emphasizes the importance of distinguishing different types of crashes and their contributing factors. We offer an indirect approach that can help to identify underlying factors and reduce bias, which can inform traffic safety methods and serve to propose effective safety countermeasures. Highlights: The injuries in hit-and-run crashes are generally less severe. Two crash types have significantly different crash exposures. The injury contributing factors are considerably different for two scenarios. It emphasizes the importance to consider crash exposure for the relevant research.